Measurement of the 234U(n,f) and 236U(n,f) cross-sections in the MeV region with MicroMegas detectors - Michalopoulou, V.; Stamatopoulos, A.; Kalamara, A.; Diakaki, M.; Axiotis, A.; Chasapoglou, S.; Kokkoris, M.; Lagoyannis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
N/A